Mary Bowser and the Civil War spy ring - Alberti, Enigma (Spy on history., 2016)
During the Civil War, African American Mary Bowser becomes a maid in the Richmond mansion of Confederate States of America president Jefferson Davis as part of a plan to pass along secrets to help the Union. May include a replica of a Confederate decoder, plus other spycraft materials, in a sealed envelope to help the reader discover clues found in the text and illustrations.